Pendidikan Kewarganegaraan sebagai Dasar Pembentukan Karakter Mahasiswa yang Kritis dan Bertanggung Jawab di Era Digital: Studi Literatur - Rohana Lubis; Nur Hakima Akhirani Nasution; Rika Puspita Hasibuan; Arini Tri Shintia Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This article discusses Civic Education as a foundation for shaping students’ critical and responsible character in the digital era. The rapid development of digital technology has influenced students’ ways of learning, communicating, accessing information, and participating in social life. However, the digital era also brings various challenges, such as hoaxes, cyberbullying, hate speech, digital ethics issues, and the lack of critical thinking in receiving information. This study uses a qualitative approach with a literature review method by examining books, journal articles, legal documents, and relevant academic sources related to Civic Education, student character, critical thinking, responsibility, digital literacy, and digital citizenship. The results of the study show that Civic Education plays an important role in strengthening students’ moral values, national awareness, legal awareness, democratic attitudes, tolerance, and social responsibility. Civic Education also contributes to developing students’ critical thinking skills in filtering digital information and building responsible behavior as digital citizens. Therefore, Civic Education needs to be developed contextually and adaptively to respond to the challenges of the digital era.